Antibody responses to the BNT162b2 mRNA vaccine in individuals previously infected with SARS-CoV-2 - Ebinger, Joseph E. (Nat Med, 2021)
In a cohort of BNT162b2 (Pfizer–BioNTech) mRNA vaccine recipients (n = 1,090), we observed that spike-specific IgG antibody levels and ACE2 antibody binding inhibition responses elicited by a single vaccine dose in individuals with prior SARS-CoV-2 infection (n = 35) were similar to those seen after two doses of vaccine in individuals without prior infection (n = 228). Post-vaccine symptoms were more prominent for those with prior infection after the first dose, but symptomology was similar between groups after the second dose.